Thailand Social Monitor on Youth : Development and the Next Generation - World Bank (Washington, DC, 2012)
This Thailand Social Monitor provides an overview of the challenges facing Thai youth today, identifying the factors that make them vulnerable and outlining possible policy directions in moving forward. This Social Monitor studies three key transitions faced by Thai youth, using the youth development model proposed by the World Development Report 2007. This model helps provide an understanding of the interactions among the various factors that affect youth development and how they influence in three important life transitions, namely: growing up healthy, learning for work and life and moving from school to work. In this model, the role of public policy is to help youth succeed in the transition to adulthood by broadening their opportunities, expanding their capacity and providing them with second chances to overcome negative outcomes. These areas are the three youth policy lenses through which policy priorities are assessed throughout this report. This report stresses that building the next generation of Thailand human capital requires a concerted effort. The four main ministries responsible for promoting the country's youth development agenda-Ministry of Social Development and Human Security, Ministry of Education, Ministry of Public Health and Ministry of Justice-must work towards ensuring that every stakeholder-including other governmental departments, NGOs and the private sector-come together to bring about an enabling environment for youth of all walks to thrive and realize their full potential. Moreover, policymaking must also be in tune with reality. It needs to listen, understand and incorporate the voices and vision of youth, the central stakeholder in this process, in order to be grounded on the will and aspirations of the next generation